Transoral laser resection or radiotherapy? Patient choice in the treatment of early laryngeal cancer: a prospective observational cohort study. Issue 6 (3rd April 2017) - Zahoor, T; Dawson, R; Sen, M; Makura, Z
Abstract: Objectives: The choices made by patients offered treatment for early laryngeal cancer with radiotherapy or transoral laser resection were reviewed. Methods: A prospective review was conducted of all patients diagnosed and treated for early laryngeal carcinoma from December 2002 to September 2009 at the Leeds Teaching Hospitals NHS Trust. A total of 209 patients with tumour stage T1 or T2 laryngeal cancer were treated; each new patient suitable for radiotherapy or transoral laser resection was seen jointly by the clinical (radiation) oncologist and head and neck surgeon, and offered the choice of treatment. Results: Of the patients, 47.4 per cent were given a choice between radiotherapy and transoral laser resection; 51.2 per cent were advised to have radiotherapy, and there were no records for the remaining 1.4 per cent. From those given the choice, 59.6 per cent chose transoral laser resection ( p < 0.02 ( t -test)) and 35.4 per cent chose radiotherapy. Conclusion: When given the choice, a statistically significant majority of patients choose transoral laser resection rather than radiotherapy.